Alternating magnetic field guiding system for MNP hyperthermia treatment of deep-seated cancers - Robert V. Stigliano; Ilona Danelyan; Giga Gabriadze; Levan Shoshiashvili; Ian Baker; P. Jack Hoopes; Roman Jobava; Fridon Shubitidze (International Journal of Hyperthermia)
Objectives Demonstrate the potential application of a novel, endoscope-like device to guide and focus an alternating magnetic field (AMF) for treating deep-seated cancers via magnetic nanoparticle hyperthermia (MNPH).Methods AMF delivery, MNP activation, and eddy current distribution characteristics are investigated through experimental studies in phantoms and computational simulations using a full 3-dimensional human model. The 3D simulations compare the novel device to traditional AMF designs, including a MagForce-like, two-coil system (used clinically) and a single surface-coil system.Results The results demonstrate that this approach can deliver the same magnetic field strength at the prostate’s centroid as traditional AMF designs, while reducing eddy current heating by 2 to 6 times. At the same level of normal tissue heating, this method provides 5.0 times, 1.5 times, and 0.92 times the magnetic field strength to the nearest, centroid, and farthest regions of the prostate, respectively.Conclusions These results demonstrate proof-of-concept for an endoscopic magnetic field guiding and focusing system capable of delivering clinically relevant AMF from a distance. This innovative approach offers a promising alternative to conventional field delivery methods by directing AMF through the body, concentrating it in the tumor region, reducing eddy currents in surrounding healthy tissue, and avoiding exposure of nearby metallic implants.